2021
DOI: 10.7759/cureus.16457
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Prevalence and Pattern of Thyroid Disorder in Pregnant Women: A Prospective Study

Abstract: BackgroundThe most frequent thyroid disorder in pregnancy is maternal hypothyroidism. The geographical variation in the prevalence of hypothyroidism during pregnancy is very wide and ranges from 2.5% to 11%. The prevalence of hypothyroidism is more in Asian countries as compared to western countries. Thus, this study was conducted to find out the prevalence of thyroid disorder in pregnancy at our center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The prevalence of hypothyroidism in our study population is similar to the reports from other low to middle-income settings [ 13 , 15 - 17 ]. A higher prevalence (16%) was however reported in Nigeria by Abdulslam K et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of hypothyroidism in our study population is similar to the reports from other low to middle-income settings [ 13 , 15 - 17 ]. A higher prevalence (16%) was however reported in Nigeria by Abdulslam K et al .…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of hypothyroidism in pregnancy varies across different ethnic groups [ 10 ]. In a low to middle-income setting, the prevalence is reported between 5 - 18% [ 11 - 13 ]. Although subclinical hypothyroidism is more prevalent than overt hypothyroidism in pregnancy, studies still report poor neurologic development in children born to mothers with any form of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Ajmani et al(29), where it was observed that the higher the BMI was associated with this disease. Furthermore, the study conducted by P. Gupta et al (30) showed that high BMI were related with both hypothyroidism and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, thyroid disorders are common during pregnancy ( 8 ). The prevalence of hypothyroidism during pregnancy varies between 2.5% and 11% ( 9 ). The main cause of thyroid disorders is iodine malnutrition (iodine deficiency or excess).…”
Section: Introductionmentioning
confidence: 99%